The relationship between income concentration and demand structure: The case of automobile demand in Spain - Holm-Detlev Köhler; José Pablo Calleja Jiménez (Atlantic Review of Economics, 2012)
Economic analysts usually look at the supply side, the evolution and distribution of GDP among sectors. However, the demand structure offers a lot of interesting information on the characteristics of an economy. The present paper analyses the relationship of growing income inequality and crisis effects on the demand structure of the Spanish automobile sector. By contrasting data on income distribution and wage structure with shifts in the car demand among different vehicle segments, some long-term trends in automobile demand are identified which are accelerated by the impact of the deep economic downturn suffered by the Spanish economy. Thus, the long-term polarization trends towards low-cost products and used cars on the one hand and luxury cars on the other contrast with the failed political efforts to foster e-vehicles by public incentives. The analysis of the demand structure of the consumer and life-style determining automotive sector allows even further insights in general economic trends and developments.
Keywords: E21; H31; L62; R22; 330; income inequality; demand structure; automotive industry; crisis effects